cDNA cloning and functional expression of the α-d-galactose-binding lectin frutalin in escherichia coli - Oliveira, Carla Cristina Marques de (2009)
cDNA clones encoding frutalin, the α-d-galactose-binding lectin expressed in breadfruit seeds (Artocarpus incisa), were isolated and sequenced. The deduced amino acid sequences indicated that frutalin may be encoded by a family of genes. The NCBI database searches revealed that the frutalin sequence is highly homologous with jacalin and mornigaG sequences. Frutalin cDNA was re-amplified and cloned into the commercial expression vector pET-25b(+) for frutalin production in Escherichia coli. An experimental factorial design was employed to maximise the soluble expression of the recombinant lectin. The results indicated that temperature, time of induction, concentration of IPTG and the interaction between the concentration of IPTG and the time of induction had the most significant effects on the soluble expression level of recombinant frutalin. The optimal culture conditions were as follows: induction with 1 mM IPTG at 22°C for 20 h, yielding 16 mg/l of soluble recombinant frutalin. SDS-PAGE and Western blot analysis revealed that recombinant frutalin was successfully expressed by bacteria with the expected molecular weight (17 kDa). These analyses also showed that recombinant frutalin was mainly produced as insoluble protein. Recombinant frutalin produced by bacteria revealed agglutination properties and carbohydrate-binding specificity similar to the native breadfruit lectin.